PHASE RELATIONS OF NATURAL PHLOGOPITE WITH AND WITHOUT ENSTATITE UP TO 8 GPA: IMPLICATION FOR MANTLE METASOMATISM - Sato K.; Katsura T.; Ito E. (My University, 1997)
Phase relations of natural phlogopite and phlogopite + enstatite compositions were determined experimentally at pressures of 4-8 GPa and temperatures of 1200-1500°C using a uniaxial split-sphere apparatus. Phlogopite in both compositions is stable in the subsolidus up to 5 GPa, and it breaks downs into pyrope, Al2O3-deficient phlogopite and fluid at pressures above 5 GPa. The Al2O3 content in phlogopite decreases from 14.4 wt% at 6 GPa to 12.9 wt% at 8 GPa, and the mode of pyrope increases concurrently from < 5 vol.% at 5 GPa to 30% at 8 GPa, in the phlogopite composition. Thus, an increase in pressure enhances two cation substitutions, Al + Al = Mg + Si and Mg + 2Al = V (vacancy) + 2Si, in the phlogopite structure. The solidi of the two compositions reach maximum temperatures of 1350°C and 1300°C, respectively, at about 5 GPa. Pyrope is a residual phase under suprasolidus conditions in both compositions above 5 GPa. These results indicate that phlogopite can be stable in garnet harzburgite in subcratonic lithosphere down to 200 km in depth. The observed decomposition of phlogopite into an assemblage of garnet and either fluid or hydrous silicate melt, suggests that phlogopite can be formed secondarily by a reaction between garnet and upwelling metasomatic agents near the base of the continental lithosphere.
Keywords: PHLOGOPITE; HIGH PRESSURE; PYROPE; METASOMATISM; LITHOSPHERE